Consumer and Community Pharmacists' Perceptions of Online Pharmacy Services in Uyo Metropolis, Nigeria - Ekpedeme Ndem; Arit Udoh; Olajide Awofisayo; Enitome Bafor (University of Minnesota Libraries Publishing, 2019)
Background: Online pharmacies benefit consumer healthcare experience through affording convenience, efficiency, greater confidentiality, and improved access to medicines. There are several online pharmacies in Nigeria, however, studies about their use as well as consumer and pharmacists' perceptions of the service are lacking. Objective: This study aimed to evaluate community pharmacists' and consumer perceptions of online pharmacy services (OPS) in Uyo metropolis, Nigeria. Method: This was a cross-sectional survey involving community pharmacists and consumers. The survey instrument was a structured, self-administered questionnaire. Survey data was analysed descriptively using frequencies and percentages while X2 was used to evaluate association between variables.  Results: In total, 60 community pharmacists and 500 consumers replied to the survey. Although the majority (>85%) of the survey respondents reported frequent internet use, only about a third (28%) of the consumers and 57% of the pharmacists were aware of the availability of online pharmacy services in Nigeria. In general, majority of the consumers were positive about using online pharmacies with approximately two thirds (67%) indicating that they would consider purchasing medicines from the service in future. Also, 83% of the consumers indicated that access to online drug information and medicine advice via the service will be valuable. There was a significant (P<0.05) association between consumers' online shopping behaviour and their likelihood to use the service. Also, majority (92%) of the community pharmacists in this survey agreed that online pharmacies promote pharmaceutical care and this perceived need was associated with their likelihood to provide the service in future (p=0.002). Consumer concerns about the service included the risk of substandard and counterfeit medicines, internet security, unavailability of prescribed brands, chances of ordering wrong medicines and uncertainty about timely delivery. Conclusion: Overall awareness of the availability of online pharmacy services in Nigeria is limited in the survey population despite reported frequent internet use in this cohort. Generally, our findings suggest the potential for future uptake of online pharmacy services and highlight the need for a standardised approach to service provision as well as a regulatory framework to improve consumer confidence and alleviate the concerns raised.   Article Type: Original Research